A Concise Review on Internet of Things: Architecture, Enabling Technologies, Challenges, and Applications - Saqib, Manasha; Moon, Ayaz H. (International Journal of Sensors Wireless Communications and Control, 2022)
Background: With the advancements of ubiquitous computing, wireless sensor networks, and machine-to-machine communication, the Internet of Things (IoT) has become a constantly growing concept. The IoT is a new paradigm that interconnects all smart physical devices to provide smart services to users. It effectively delivers user-required services by utilising internet connectivity, sensors, and various technologies and protocols for the analysis and collection of data. IoT is predicted to permeate practically every facet of daily life, from smart cities to health care, smart agriculture, logistics and retail, and even smart living and smart ecosystems. Since IoT systems are comprised of heterogeneous hardware and networking technologies, integrating them to the software/ application level to extract information from massive amounts of data is a difficult task. Methods: In this survey, the definitions, elements, working, architecture, fundamental technologies, key challenges, and potential applications of IoT are systematically reviewed. Initially, the various definitions and elements of IoT are introduced, followed by an explanation of how an IoT works. Additionally, an outline of IoT in the context of the architecture is presented. The primary enabling technologies that will drive IoT research in the near future are examined in this paper. Furthermore, the major key challenges that the research community must address, as well as potential solutions, are investigated. Finally, the paper concludes with some potential IoT applications to demonstrate the concept's feasibility in real-world scenarios. Conclusion: The goal of this survey is to assist future researchers in identifying IoT-specific challenges and selecting appropriate technology based on application requirements.
Keywords: architecture